Dinasti Mamalik di Mesir - Darmalaksana, Wahyudin (UIN Maulana Malik Ibrahim Malang, 2009)
This paper intends to explore the historical aspect of Mamalik dynasty. It was associated with Daulah Islamiyah in Mesir which lead by slave group (Mamalik) from 13th century up to 16th A.D that became one of unique Islamic political faces. At that time, civil society can form themselves as military power driven by slavers. Retired slavers emerged as political elite and bodyguard of Sultan. Mamalik group divided into two groups. First, Mamalik Bahriyah coming from middle Asia, especially Turkey Qipsaq. Second, Mamalik Burjiyah coming from Sirkasia race in·Kaukasus (East Europe). Historically, Mamalik Dynasty in Mesir classified into three periods. First, the period of Mamalik government formation which was